Współczesne tendencje zmian w systemie kontroli w przedsiębiorstwie - Skorb-Gała, Alina (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Nowadays, control is becoming one of the most important part of management of enterprises. Managers constantly improve systems of control and search for the best solution of organizations in control systems. The paper presents contemporary tendencies of changes in control systems and mentions propositions of control systems from literature. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 280-285